2020
DOI: 10.5194/bg-2020-202
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of dust enrichment on Mediterranean plankton communities under present and future conditions of pH and temperature: an experimental overview

Abstract: Abstract. In Low Nutrient Low Chlorophyll areas, such as the Mediterranean Sea, atmospheric fluxes represent a considerable external source of nutrients likely supporting primary production especially during stratification periods. These areas are expected to expand in the future due to lower nutrient supply from sub-surface waters caused by enhanced stratification, likely further increasing the role of atmospheric deposition as a source of new nutrients to surface waters. Yet, whether plankton communities wil… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(45 citation statements)
references
References 0 publications
3
42
0
Order By: Relevance
“…This was confirmed by the 14 C-based particulate production rates, which were about half the ones measured at the other two stations. The community at TYR was most likely relying on regenerated nutrients, as shown by the highest levels of ammonium (NH4 + ) measured at the start of this experiment (Gazeau et al, 2020). As discussed in Guieu et al…”
Section: Inorganic and Organic Materials Exportmentioning
confidence: 63%
See 2 more Smart Citations
“…This was confirmed by the 14 C-based particulate production rates, which were about half the ones measured at the other two stations. The community at TYR was most likely relying on regenerated nutrients, as shown by the highest levels of ammonium (NH4 + ) measured at the start of this experiment (Gazeau et al, 2020). As discussed in Guieu et al…”
Section: Inorganic and Organic Materials Exportmentioning
confidence: 63%
“…Phytoplankton communities at stations TYR and ION were dominated by Prymnesiophytes followed by Cyanobacteria, while, at station FAST, the phytoplanktonic community was clearly dominated by photosynthetic prokaryotes. At all three stations, the proportion of pigments representative of larger species was very small (< 5%; Gazeau et al, 2020). Heterotrophic prokaryotes were the most abundant at station FAST (6.15 x the percentage of extracellular release (%PER) did not exceed 45%.…”
Section: Initial Conditionsmentioning
confidence: 89%
See 1 more Smart Citation
“…Thus, the difference between Km 1 and Km all might reflect adaptive strategies to spatial and/or temporal patchiness in the distribution of suspended particles. Freshly sinking material was probably not present in our incubations because of the small volume of water used but could have contributed to the release of free bacteria, small suspended particles and DOM within its associated plume (Azam and Long, 2001;Tamburini et al, 2003;Grossart et al, 2007;Fang et al, 2015). Baltar et al (2009a) also suggested that hot spots of activity at depth were associated with particles.…”
Section: How the Set Of Concentrations Used Affects Ectoenzymatic Kinetic Trends With Depth: Possible Links With Access To Particlesmentioning
confidence: 99%
“…We compared the in situ LAP hydrolysis rates to the N demand of heterotrophic prokaryotes (which was based on BP data assuming no active excretion of nitrogen and a C/N ratio of 5). Similarly, the in situ rates of TAAs plus TCHOs were compared to the bacterial carbon demand (based on a bacterial growth efficiency of 10 %; Gazeau et al, 2020;Céa et al, 2014;Lemée et al, 2002). Using the global model, in situ hydrolysis of TAAs by LAP contributed only 25 % ± 22 % of the bacterial N demand in epipelagic layers and 26 % ± 24 % in deep layers.…”
Section: How the Set Of Concentrations Used Affects Potential Contribution Of Macromolecule Hydrolysis To Bacterial Productionmentioning
confidence: 99%